Letters to Bhutan: A Living Inquiry Into Bhutanese Students’ Cross-Cultural Adaptations in Canada - Robertson, Hannah; Lin, Ching-Chiu; Sherab, Kezang; Dema, Chimi (Comparative and International Education / Éducation comparée et internationale, 2026)
This study explores the lived experiences of Bhutanese international students pursuing higher education in Canada. Grounded in Gross National Happiness (GNH) as a conceptual foundation and using Karen Meyer’s living inquiry framework alongside Young Yun Kim’s cross-cultural adaptation theory, we examine how students navigate cultural transitions through four interconnected dimensions: place, language, time, and self/other. Employing creative methodology through narrative reconstruction in the form of letters to home, this research reveals complex negotiations between GNH values and Western educational paradigms. Findings suggest that students navigate complex adaptation processes across spatial, temporal, and communicative dimensions while developing intercultural identities that integrate heritage and host cultural elements through creative coping strategies. Structural factors including immigration policy, institutional support, and financial pressures significantly shape these adaptation processes. This study contributes to comparative education literature by examining an understudied population and showing how small-nation students navigate globalized higher education through sophisticated meaning-making processes that require targeted institutional support.